"If It Wasn't for Ethics, I Wouldn't Go Near Him": An Interpretative Phenomenological Analysis of Caring for Patient-Prisoners in Kenya. (October 2019) - Muiruri, Peninnah Njeri; Brewer, Gayle; Khan, Roxanne
Those caring for patient-prisoners experience distinct challenges that may impede effective treatment. Previous studies have investigated these issues from the perspective of forensic or correctional nurses, yet overlooked the lived experiences of nurses based in public health hospitals caring for patient-prisoners. In this study, semi-structured interviews were conducted with five nurses caring for patient-prisoners in public hospitals in Kenya. Interviews were analysed using interpretative phenomenological analysis. Four superordinate themes were identified: fear of patient-prisoner, time constraint, labelling, and optimism on recidivism. The fear of patient-prisoner theme included two sub-themes: perceived dangerousness and communication hindrance. The time constraint theme included three sub-themes: workload, short hospital stay, and task-oriented system. The labelling theme contained the loss of individual identity and representative of a group of sub-themes. Optimism on recidivism involved two sub-themes: reformation and rebuilding one's life. Future research should investigate the extent to which these impact on the patient-prisoner experience.